(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2026)
This article highlights the pedagogical capabilities of using artificial intelligence technologies in the process of teaching design problems in construction drawing. Furthermore, it analyzes the methodology for developing students’ creative thinking, visual imagination, and professional competencies through AI.